A metacognição aplicada ao ensino coletivo da clarineta - Cruz, Francisca Antonia Marcilane Gonçalves (2023)
This thesis sought to verify if - and in what way a metacognitive pedagogical experience could affect the musical education of beginning clarinetists in a context of collective teaching and learning. To that end, we propose an experiment developed from a pedagogical intervention. Our main space of operation was the Otacílio Barbosa dos Santos Municipal Music Band, associated to the Paraipaba Municipal Hall, in the countryside of the state of Ceará, with the research subjects being a group of clarinet players who had recently joined this band. The research had a qualitative character and used the pseudo-experimental design as a method of evaluation and analysis. In this sense, we analyzed the relation between the independent variables (incentive to the awareness of learning processes) and dependent variables (metacognitive abilities of clarinet students). Our experimental group was the clarinet class of the Paraipaba band, and the control group, our previous experiences related to the traditional teaching of clarinet and the approaches of the specialized literature on the subject. Our pedagogical proposal had as a differential the offer of metacognitive stimuli for the improvement of students’ cognitive abilities on the clarinet. The proposed teaching methodology was systematized and self-reflexive, centered on physical practice allied to mental practice, because we believe that students who are reflective and aware of their learning process can become more autonomous and active subjects in the construction and reconstruction of their knowledge. During this study we created and used didactic support material, namely: the Metacognitive guide to the initial learning of the clarinet and the Practice diary. We identified the total of T = 267 indications of metacognitive abilities of clarinet students, which were more evident when the clarinet teacher employed some type of stimulus. That fact confirmed the hypothesis that the more stimuli to the awareness of learning processes in clarinet classes, the greater the development of metacognitive skills of students. We hope, through the results obtained with this study, to contribute to the improvement of the practice of music educators, conductors, instrumentalists in general and, primarily, clarinetists at the initial level of learning, assisting them in accessing and using their metacognitive abilities.